2019
DOI: 10.1364/oe.27.010981
|View full text |Cite
|
Sign up to set email alerts
|

High-power quantum-dot superluminescent tapered diode under CW operation

Abstract: A high-power quantum-dot superluminescent diode is demonstrated under continuous-wave operation, with an output power of 137.5 mW and a corresponding spectral bandwidth of 21 nm. This represents not only the highest output power, but also a record-high power spectral density of 6.5 mW/nm for a CW-operated superluminescent diode in the 1.1-1.3 μm spectral region, marking more than a 6-fold increase with respect to the state of the art. The two-section contact layout of the reported device introduces additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Reproduced with permission. [136] Copyright 2018, Optica Publishing Group. e) Schematic diagram of SLD with a tapered waveguide.…”
Section: Edge Emittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [136] Copyright 2018, Optica Publishing Group. e) Schematic diagram of SLD with a tapered waveguide.…”
Section: Edge Emittingmentioning
confidence: 99%
“…This device shows a high output power of 137.5 mW, and a highpower spectral density of 6.5 mW nm −1 in the 1.1-1.3 μm spectral region. [136] In addition to the above single-section devices, there are many manufacturing steps for multisection devices, and the operation is complicated due to multiple arrangements of drive currents. But the multisection device allows customized emission spectra and longitudinal multiplexing.…”
Section: Edge Emittingmentioning
confidence: 99%
“…[18] For QD-SLDs with a central wavelength in the O-band, and utilizing the common contribution of GS and ES to broaden the spectrum, their spectrum dip is not less than 0.2 dB. [19][20][21] In addition, it is found that doping technology is often used to improve the performance of QD-SLDs, such as p-type modulation doping technology. [22] However, it can only increase the output power, but not broaden the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…< using a broadband emitting QDSLD [17]. To this day, effort is being put into developing more efficient and high-powered QDSLDs [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%